Software architecture design of the information technology for real-time business process monitoring - Batyuk, A.; Voityshyn, V. (My University, 2018)
Having precise understanding of how business processes are performed in real-life is an important input for decision makers and consequently is a strong competitive advantage for an organization. In the constantly changing modern business environment it is crucial to provide that information as soon as possible, preferably in the real-time mode. In practice, such kind of tasks are usually resolved by means of Business Intelligence solutions implemented either from scratch or based upon customizable packages. Despite of the wide range currently available types of data visualizations, modern BI solutions still lacks features to represent data obtained from process-aware systems, for example control flow charts. Current paper is devoted to the information technology for real-time business process monitoring. The represented solution is an extendable software which is based on the lambda architecture and a streaming process discovery technique.
Keywords: information technology; process mining; streaming process discovery; lambda architecture; Heuristic Miner